Pengaruh Edukasi 3R Terhadap Perubahan Perilaku Pengelolaan Sampah Pada Masyarakat Desa Dendun Kabupaten Bintan - Simbolon, Veronika Amelia; Nadeak, Erpina Santi Meliana; Fakhira, Nabila Yasmin; Putri, Nurfadilahni’mah; Ningrum, Livia (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2025)
Indonesia, with its majority archipelago, faces serious challenges in sanitation and waste management, especially in coastal areas. Low public awareness, the habit of dumping waste into the sea, and limited infrastructure exacerbate environmental conditions and have an impact on public health. This community service activity aims to evaluate the effect of 3R (Reduce, Reuse, Recycle) concept education on changes in waste management behavior in Dendun Village, Bintan Regency. Education was conducted interactively using PowerPoint and video media, accompanied by composting and ecobricking practices as simple solutions that are applicable to coastal communities. Evaluation was conducted through pre-test and post-test using questionnaires to 30 respondents. Results showed a significant increase in community knowledge, from 56.7% (poor category) to 80% (good), and behavior change from 46.7% (poor) to 83.3% (good). Statistical tests showed p values <0.05 in all variables, which means that there is a significant effect of education on improving knowledge, behavior, skills, and support for sanitation management. Based on the results described, it can be concluded that 3R education is effective in increasing awareness and waste management practices at the community level. This program is expected to be a model for empowering coastal communities in an effort to preserve the environment and improve health status.